Takaful sinar ihsan plus / Nur Adibah Ab Aziry ... [et al.] - Ab Aziry, Nur Adibah; A.Rahman, Erlyn Marlina; Mohamad Ridzuan, Nurul Izzaty; Mohammad Hatta, Mohammad Firdaus (2021)
Takaful is a scheme based on brotherhood, unity and mutual aid that provides financial aid and assistance to participants when needed. Participants also agreed to give contributions for that purpose. Takaful is based on the origin of Ta'awun (cooperation) and Tabarru' where the hazard is bestowed collectively by members of a policy. Takaful is an alternative to conventional insurance, and its primary objective is to protect the participants based on the ethical and moral foundations. The purposes of this study are to help orphans and poor children who are under the care of private shelters to plan for a better future after reaching the age of 18 years old, as well as to introduce and encourage the community especially philanthropists with a new method in obtaining takaful plans for orphans and the poor. To achieve these purposes, researchers believe that both quantitative and qualitative methods are suitable and appropriate for this study. It is possible to combine quantitative and qualitative methods, although great care should be taken to ensure that the theory behind each method is compatible and that the methods are being used for appropriate reasons. The questionnaires were distributed to 40 public people as respondents within Selangor area. Moreover, the finding shows that three variables in which attitude, subjective norm and perceived behavioral control are related to the people's intentions to participate in orphans' takaful. This product is great to set up to help orphans get a better life after reaching 18 years of age. In addition, this product helps philanthropists getting a special platform to channel their donations. It is hoped that this Takaful Sinar Ihsan Plus plan can help philanthropists to make savings with a very lucrative return on investment in the hereafter compared to worldly savings alone. From this product, it actually can train the community to take care of the orphans' welfare and their right to get medical and education coverage. So, it is very worthwhile if takaful operators can create products to help the needy especially for the orphans.